A new ex vivo human oral mucosa model reveals that p38MAPK inhibition is not effective in preventing autoantibody‐induced mucosal blistering in pemphigus. (4th September 2019) - Egu, D.T.; Sigmund, A.M.; Schmidt, E.; Spindler, V.; Walter, E.; Waschke, J.
Summary: Background: Pemphigus vulgaris (PV) is an autoimmune disease characterized by blister formation in the epidermis and oral mucosa due to loss of keratinocyte cohesion. Autoantibodies present in patients with PV (PV‐IgG) are known to primarily target desmoglein (Dsg)1 and Dsg3 in desmosomes. The mucosal‐dominant subtype of PV (mdPV) is caused by PV‐IgG autoantibodies against the cadherin‐type adhesion molecule Dsg3. p38 mitogen‐activated protein kinase (p38MAPK) signalling has been characterized as an important pathway downstream of PV‐IgG binding and its inhibition is protective in ex vivo human skin. However, the role of p38MAPK signalling in mdPV is unknown as no experimental model has been available. Objectives: To establish a human ex vivo oral mucosa culture, and evaluate the p38MAPK dependency of blister formation and of ultrastructural alterations of desmosomes induced by mdPV‐IgG. Methods: Human labial mucosa was injected with mdPV‐IgG as well as AK23, a pathogenic mouse monoclonal Dsg3 antibody, in the presence or absence of p38MAPK inhibitors. Viability was evaluated by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay and apoptosis by terminal deoxynucleotidyl transferase dUTP nick‐end labelling assay. Blister score was determined following haematoxylin and eosin staining and Dsg3 distribution by immunostaining. Samples were processed for transmission electron microscopy to analyse desmosome ultrastructure. Results: Both AK23 and mdPV‐IgG induced blisters and caused reduction in desmosome size and number in labial mucosa. Inhibition of p38MAPK was not effective in preventing these alterations. Conclusions: In contrast with human epidermis, PV‐IgG and AK23 induce blisters and desmosome ultrastructural changes in labial mucosa via a mechanism not dependent on p38MAPK. What's already known about this topic? Pemphigus vulgaris IgG (PV‐IgG) induces blistering as well as a reduction in desmosome number and size mediated by p38 mitogen‐activated protein kinase (p38MAPK) signalling in ex vivo human skin. What does this study add? This study establishes a new human ex vivo mucosa model to test pathomechanisms mediated by PV‐IgG. The study demonstrates that both AK23 and mucosal‐dominant PV induce blisters and associated ultrastructural changes in labial mucosa via a mechanism not dependent on p38MAPK signalling. What is the translational message? This study highlights the respective tissue‐specific responses of oral mucosa and skin related to PV pathogenesis, similar to the patient situation. Abstract : Respond to this article Linked Comment: Ludwig. Br J Dermatol 2020; 182 :833–834.